2011
DOI: 10.1159/000334432
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Phase II Randomized Trial of Docetaxel/Gemcitabine versus Docetaxel/Capecitabine as First-Line Treatment for Advanced Breast Cancer: A Gruppo Oncologico Italia Meridionale Study

Abstract: Objective: To evaluate two docetaxel-based regimens as first-line treatment in advanced breast cancer patients. Methods: Patients were randomly assigned to docetaxel/gemcitabine (arm A: docetaxel 75 mg/m2 on day 1, gemcitabine 1,000 mg/m2 on days 1 and 8) or docetaxel/capecitabine (arm B: docetaxel 75 mg/m2 on day 1, capecitabine 1,250 mg/m2 twice daily on days 1–14); both chemotherapy regimens were repeated every 21 days. The primary objective of the study was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Efficacy outcomes of this regimen are in the range of data reported for docetaxel and capecitabine combination. In the first-line setting this combination is reported to provide a PFS duration of 8.5-10 months and an ORR of 39-74% (12,13). Although a control arm was not included in the present study, the TTP following 6 cycles of taxane with combination therapy without maintenance was 3.8 months in a previous study (14).…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy outcomes of this regimen are in the range of data reported for docetaxel and capecitabine combination. In the first-line setting this combination is reported to provide a PFS duration of 8.5-10 months and an ORR of 39-74% (12,13). Although a control arm was not included in the present study, the TTP following 6 cycles of taxane with combination therapy without maintenance was 3.8 months in a previous study (14).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, neutropenia and hand-foot syndrome (HFS) were the most common adverse events, followed by mucositis and diarrhea. These adverse effects are well known from both the previous studies [7][8][9][10][11][12][13][14][15][16][17] and everyday practice. In the pivotal phase III trial gastrointestinal side effects and HFS occurred more frequently in patients receiving combined chemotherapy [9].…”
Section: Discussionmentioning
confidence: 85%
“…XT combination was significantly superior to docetaxel monotherapy, with significantly superior ORR, TTP, and OS as compared to single-agent docetaxel [9]. The subsequent randomized trials in first-, second-and third-line settings using the same regimen achieved TTP/PFS of 7.9-10 months, median overall survival (OS) of 16.4-28 months and ORR of 38.9-68 % [10][11][12][13]. Despite the differences in patient populations, the regimens and the response criteria applied, our data are comparable with these results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…'s study [ 26 ] and Seidman et al 's study [ 23 ]. For these reasons, we excluded above six studies and enrolled the rest 15 studies [ 12 18 , 26 33 ] in our systematic review (The Selection flow was is shown in Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%